Nilai Moral Kristiani dalam Ukiran Figuratif Sa’o Ngaza pada Masyarakat Ngada Nusa Tenggara Timur - Paskalis Lina; Raymundus I Made Sudhiarsa (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
This article focuses on extracting one of the local wisdom, namely, figurative carvings on the traditional house (sa’o ngaza) of the Ngada community, East Nusa Tenggara, and reviewing it from the perspective of Christian moral theology. The method used is a qualitative one, employing especially a phenomenological approach and a narrative approach. The data are obtained from direct interviews with key informants who understand the figurative carvings on traditional houses and come from several villages in the Ngada Flores Regency, East Nusa Tenggara. The results show that the figurative carvings contain moral values, such as discipline, hard work, responsible leadership and integrity, loyalty, and sacrifice. These values can be called local wisdom and can be used as a reference for knowledge and understanding for developing moral character to overcome the leadership and social crises that still plague Indonesian society today.